2021
DOI: 10.1007/s10802-021-00851-8
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Trajectories of Internalising, Externalising, and Peer Problems Across Childhood: a Person-centered Approach

Abstract: This study investigated trajectories of concomitant internalising, externalising, and peer problems, and associated risk factors for group-membership, using a person-centered approach to better understand heterogeneity in subgroups identified. A cohort of 7,507 children in Ireland was followed from infancy to late childhood (50.3%, males; 84.9% Irish). The parent-version of the Strengths and Difficulties Questionnaire was used when children were 3, 5, 7 and 9 years of age. Information on antecedent risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 86 publications
(119 reference statements)
4
12
0
Order By: Relevance
“…The non-engager and the normative group, a combined estimated 38.2% of children in the sample, exhibited low or declining symptoms in conduct problems, hyperactivity/inattention, and peer problems. These two low risk groups are in line with previous findings in the developmental literature (e.g., Fanti & Henrich, 2010;Girard, 2021;Patalay et al, 2017), suggesting that behavioural problems in preschool children may be normative, particularly as children enter into the classroom setting and are learning to navigate social relationships with peers. For most children, these early difficulties are expected to decline as higher-order skills are better developed, resulting in low-risk trajectories of externalising behaviours and peer problems after entry into formal schooling.…”
Section: Group-based Multi-trajectoriessupporting
confidence: 89%
See 4 more Smart Citations
“…The non-engager and the normative group, a combined estimated 38.2% of children in the sample, exhibited low or declining symptoms in conduct problems, hyperactivity/inattention, and peer problems. These two low risk groups are in line with previous findings in the developmental literature (e.g., Fanti & Henrich, 2010;Girard, 2021;Patalay et al, 2017), suggesting that behavioural problems in preschool children may be normative, particularly as children enter into the classroom setting and are learning to navigate social relationships with peers. For most children, these early difficulties are expected to decline as higher-order skills are better developed, resulting in low-risk trajectories of externalising behaviours and peer problems after entry into formal schooling.…”
Section: Group-based Multi-trajectoriessupporting
confidence: 89%
“…Three factors were common for elevated groups and included child sex, receptive language skills, and belonging to single parent households. In line with the literature (e.g., Girard, 2021;Girard et al, 2019;Teymoori et al, 2018), boys were more likely to belong to elevated groups with the largest odds (i.e., 3.1 higher odds) of belonging to the multimorbid moderate-high chronic group. It has been suggested that social determinants for males and females, such as parental and environmental socialisation, impact gender roles behaviours and, in turn, sex differences in childhood problems .…”
Section: Risk and Protective Factors For Group Membershipsupporting
confidence: 88%
See 3 more Smart Citations